IMPLEMENTING CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOLS: A CFIR ANALYSIS OF THE NISAIYAH PROGRAM AT AN-NUR DARUNNAJAH 8, INDONESIA - Muhamad Towil Akhirudin; Wianda Rahman; Muchammad Ibnu Muzakir; Arief Ardiansyah; Anas Fauzi (Hijri, 2025)
This study analyzes the implementation of the Nisaiyah Program at Pondok Pesantren An-Nur Darunnajah 8 Cidokom, Indonesia, a character education initiative specifically designed for female students (santri). It aims to evaluate the enabling factors, barriers, and overall effectiveness of the program in achieving its holistic character education objectives. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis. Thematic analysis was applied, with data validity ensured via source triangulation. The findings reveal that while the Nisaiyah Program is underpinned by a sound conceptual design and strong leadership commitment, its effectiveness is significantly constrained by systemic challenges. Key impediments include inconsistent curriculum delivery, inadequate physical resources, a lack of a structured mentoring system, and managerial inefficiencies such as a saturated schedule and diffuse management ownership. Analysis through the lenses of the Consolidated Framework for Implementation Research (CFIR) and Total Quality Management (TQM) principles demonstrates how the interplay of barriers within the inner setting and implementation process curtails the program's potential. The study concludes that the success of educational innovations within Islamic boarding schools necessitates a synergistic alignment of vision, robust operational systems, and dedicated resource allocation. The implications call for systemic improvements in curriculum fidelity, mentoring frameworks, and infrastructure. Future research should pursue longitudinal studies on the program's long-term impact, comparative case studies across pesantren, and investigations into strategies for cultivating positive peer cultures that reinforce program objectives